(untitled) (Journal of Asian Development Studies, 2025)
Initially rooted in navigation, triangulation refers to determining an object’s position from multiple reference points, as in maritime navigation. In research, this concept has been adapted to integrate diverse theoretical or methodological perspectives, providing multiple interpretations of a single research problem. This approach enables researchers to construct varied perspectives, enriching depth, credibility, and validity of findings. Scholars define triangulation as the application of multiple approaches to examine a single issue. This paper will provide various perspectives of methodological triangulation to the graduate students, particularly those in the early stages of their academic careers. It explores its historical evolution, conceptual foundations, primary classifications, and the practical applications of methodological triangulation. Additionally, it identifies the challenges associated with methodological triangulation and presents strategies to help young researchers effectively integrate the triangulation approach, thereby enhancing the quality of their mixed-method research. Furthermore, the findings of methodological triangulation are critically analyzed and discussed through selected examples from health and social sciences research (Mousazadeh et al., 2019; Egerod et al., 2020; Raymond et al., 2018), demonstrating its real-world relevance and guiding students in applying rigorous, multidimensional approaches to complex research problems.